Preliminary Insights into SMEs Opportunities and Vulnerabilities in the European Context. A Qualitative Approach - VĂTĂMĂNESCU, Elena - Mădălina; GORGOS, Elena-Alexandra; ALEXANDRU, Vlad-Andrei (Management Dynamics in the Knowledge Economy, 2018)
The current study aims to theoretically investigate the opportunities and vulnerabilities apposite for the small and medium-sized enterprises (SMEs), insisting on the internationalization conditions, and to empirically explore the European initiatives meant to support the SMEs in their various endeavors, from accessing relevant knowledge to deploying successful operations in foreign markets. To this end, a qualitative research was conducted through the case study method. Over 10 European initiatives were described and more than 20 relevant documents available on official European websites were analyzed. The underlying assumption for conducting this study resided in the fact that a better understanding of the European context describing SMEs performance would provide valuable insights to the actors interested in their future business activity, specifically in their cross-border projects and operations. Moreover, a refined outlook would enlarge their vision of the existing opportunities and thus catalyze the process of converting current challenges into positive results.